Estudo numérico e experimental das rigidezes de contato de uma estrutura de espelho da linha Mogno do Sirius - Silva, Dante Vecchia Rocha (Universidade Federal de São Carlos, 2021)
One of the challenges in the project of new 4th generation synchrotron light sources, such as Sirius (LNLS), is the design of the mechanical stability of the components of the new beamlines, where it is possible to carry out experiments with nanometer sized light beams. With the existence of mechanical vibrations inherent to the process in all its stages, it is necessary to reduce its effects as much as possible, as they directly affect the beam stability and may cause a loss of beamline resolution. A crucial step in the stability assessment is the modal analysis, in which it is important to know and use adequate contact stiffness values to ensure the quality of the design. As it is a complex concept and dependent on several factors, such as material stiffness, contact roughness, body bond strength, surface quality, among others, it is difficult to obtain analytically reliable results and even to replicate studies carried out in different projects. Therefore, the purpose of this study is to acquire the coherent values of the contact stiffnesses of one of the mirror structures of the Mogno Line, which is being projected to be the world leader in micro and nano images using X-rays, through a methodology that combines an experimental modal analysis of the system with a numerical optimization study using the Ansys program. Finally, identify the most sensitive contacts for the system and propose changes in geometries to improve mechanical stability. The values found in this work can be used in beamline projects in the future. Keyword: Contact Stiffness. Sirius. Mechanical Vibrations. Model Updating.
Theorical and experimental study of contact stiffnesses of one of the mirror structures of the Mogno Line from SIRIUS.
Keywords: Rigidez de contato; Vibrações mecânicas; Ajuste de modelo; Sirius; Contact stiffness; Mechanical vibrations; Model updating; ENGENHARIAS::ENGENHARIA MECANICA::PROJETOS DE MAQUINAS